Patient satisfaction and associated factors with services provided at outpatient departments - Dereje Mesfin; Tadiwos Gintamo (International Journal of Public Health Science (IJPHS), 2019)
Asking patients what they think how they feel about the health service they have received is an important step towards improving the quality of care and, ensuring that local health services are meeting clients needs and expectations. Facility- based cross-sectional study was conducted from April 1-7, 2019 in randomly selected primary hospitals found in Guraghe zone. There were 266 randomly selected patients who attended the primary hospitals were participated in the study. Data was collected using a interviewer-administered structured questionnaire and analyzed using SPSS version 21. Multiple logistic regression analysis used to identify predictors of patient satisfaction. The overall of patient satisfaction level with the health service provided at the outpatient departments of the primary hospitals was 66.5% (95% C.I. 60.8%-72.2%). waiting time (AOR 3.65), informing patients about cause of illness (AOR, 2.46) and waiting area cleanliness (AOR 2.33) were among the significant predictors of patients satisfaction. Acknowledging the limitation of the cross-sectional study design findings of this study indicate that waiting time, telling the cause of illness, cleanliness of the waiting area are important predictors of patient satisfaction.